Active surveillance for localized prostate cancer: An analysis of patient contacts and utilization of healthcare resources. (February 2015) - Thomsen, Frederik B.; Berg, Kasper D.; Røder, M. Andreas; Iversen, Peter; Brasso, Klaus
Abstract Objective. Evidence supports active surveillance (AS) as a means to reduce overtreatment of low-risk prostate cancer (PCa). The consequences of close and long-standing follow-up with regard to outpatient visits, tests and repeated biopsies are widely unknown. This study investigated the trajectory and costs of AS in patients with localized PCa. Materials and methods. In total, 317 PCa patients were followed in a prospective, single-arm AS cohort. The primary outcomes were number of patient contacts, prostate-specific antigen (PSA) tests, biopsies, hospital admissions due to biopsy complications and patients eventually undergoing curative treatment. The secondary outcome was cost. Results. The 5 year cumulative incidence of discontinued AS in a competing-risk model was 40%. During the first 5 years of AS patients underwent a median of two biopsy sets, and patients were seen in an outpatient clinic including PSA testing three to four times annually. In total, 38 of the 406 biopsy sessions led to hospital admission and 87 of the 317 patients required treatment for bladder outlet obstruction (BOO). With a median of 3.7 years' follow-up, the total cost of AS was euro (€) 1, 240, 286. Assuming all patients had otherwise undergone primary radical prostatectomy, the cost difference favoured AS with a net benefit of €662, 661 (35% reduction). Conclusions. AS entails a close clinical follow-up with a considerable risk of rebiopsy complication, treatment of BOO and subsequent delayed definitive therapy. This risk should be weighed against a potential economic benefit and reduction in the risk of overtreatment compared to immediate radical treatment.